2020
DOI: 10.5586/aa.7337
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Temperature and Potassium Fertilizer on the Growth, Yield, and Biochemical Parameters of Ipomoea batatas var. Antin-1

Abstract: The impact of temperature and potassium fertilizers on the growth, yield, and basic biochemical characteristics of sweet potato, <em>Ipomoea batatas </em>var. Antin- 1, was investigated in lowland and highland terrains. In this study we aimed to determine the different traits of the sweet potato, based on its morphology, physiology, and biochemical composition, following treatments with a potassium fertilizer at different temperatures. The study was undertaken using a nested factorial design. The f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…For example, the positive effect is observed in apple ( Solhjoo et al, 2017 ) and olive ( Zivdar et al, 2016 ), whereas no effect is reported in red cabbage ( Piccaglia et al, 2002 ), purple corncob ( Jing et al, 2007 ), and Melastoma malabathricum ( Koay et al, 2014 ). In addition, a quadratic function of K fertilizer to anthocyanin is documented in batatas ( Sulistiani et al, 2020 ) as well. The discrepancy of anthocyanin accumulation for plants might be ascribed to the varied anthocyanin composition of a specific plant per se .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the positive effect is observed in apple ( Solhjoo et al, 2017 ) and olive ( Zivdar et al, 2016 ), whereas no effect is reported in red cabbage ( Piccaglia et al, 2002 ), purple corncob ( Jing et al, 2007 ), and Melastoma malabathricum ( Koay et al, 2014 ). In addition, a quadratic function of K fertilizer to anthocyanin is documented in batatas ( Sulistiani et al, 2020 ) as well. The discrepancy of anthocyanin accumulation for plants might be ascribed to the varied anthocyanin composition of a specific plant per se .…”
Section: Discussionmentioning
confidence: 99%
“…It is widely known that litchi loses its brilliant red appearance soon at ambient condition after harvest and extensive efforts are made to solve this phenomena ( Zhang et al, 2005 ; Fang et al, 2015 ), however, the role of pericarp pigmentation enhancement through foliar nutrient application preharvest is scarcely investigated in litchi. Potassium (K) is frequently supplemented to enhance the pigmentation in plants due to its multiple reactive functions in higher plants ( Nguyen et al, 2010 ; Sulistiani et al, 2020 ). Thus, this study is to evaluate the role of foliar nutrient spray on pericarp pigmentation, and explore the relation between human visual color preference and pigment composition in litchi fruit pericarp, with the objective to identify an effective mineral nutrient salt to improve litchi pericarp color.…”
Section: Introductionmentioning
confidence: 99%
“…The average use of Phonska fertilizer in the research area is 349 kg per hectare. In multi-site research, potassium doses cause differences in anthocyanin content, anthocyanin production, and sweet potato glucose production [42]. K application is positively correlated with the accumulation of sweet potato starch.…”
Section: A Production Function Analysis Of Stochastic Frontiermentioning
confidence: 99%
“…Previous research has revealed inconsistent responses of sweet potatoes to K fertilization. Some demonstrate no impact of increased K fertilization rate [11,12] whereas others report splitting K fertilization application across the growing season positively impacts yield [13]. However, the previous authors collectively failed to report fertilizer recommendations based on soil tests and utilized K fertilization rates far below those typically recommended for sweet potato production in the United States [8].…”
Section: Introductionmentioning
confidence: 99%